EKSPLORASI DAN KARAKTERISASI ENTOMOPATOGEN ASAL BERBAGAI INANG DAN LOKASI - Tri Puji Priyatno; I Made Samudra; Ifa Manzila; Dwi Ningsih Susilowati; Yadi Suryadi (Research Center for Biology-Indonesian Institute of Sciences, 2016)
Microbial groups of entomopathogenic (fungi and bacteria) had been reported causing insect mortality. The aim of the study was to explore and characterized entomopathogenic from various host and locations. Fungal identification at genus and species level was caried out based on conidial morphology, hyphal growth, conidiophore and colony color; whilst for bacterial identification was based on standard Bergey’s manual for determinative bacteria. Sixteen entomopathogenic isolates that consisted of fungal and bacteria have been collected and preserved for further characterization. Of the 16 entomopathogen collected samples, five fungal genera was found i.e. Paecilomyces; Metarhizium, Beauveria, Hirsutella; and Cordyceps. Seven isolates belonging to six fungal isolates, and one bacterial isolate had been identified based upon ITS and 16S rDNA sequences, respectively. We confirmed that 6 fungal isolates belong to species of Paecilomyces reniformis, B. bassiana, M. anisopliae, M. anisopliae var acridum, Hirsutella thomsonii. One isolate of red pigmented bacteria Sm201102 have been identified was belonging to species Seratia marcescence. It was also obtained two fungal isolates from different host (spider and beetle) which confirmed by morphological character belong to Cordyceps sp.